Lessons Learned from the Studies of Roots Shaded from Direct Root Illumination - Lacek, Jozef; García-González, Judith; Weckwerth, Wolfram; Retzer, Katarzyna (International journal of molecular sciences, 2021)
The root is the below-ground organ of a plant, and it has evolved multiple signaling pathways that allow adaptation of architecture, growth rate, and direction to an ever-changing environment. Roots grow along the gravitropic vector towards beneficial areas in the soil to provide the plant with proper nutrients to ensure its survival and productivity. In addition, roots have developed escape mechanisms to avoid adverse environments, which include direct illumination. Standard laboratory growth conditions for basic research of plant development and stress adaptation include growing seedlings in Petri dishes on medium with roots exposed to light. Several studies have shown that direct illumination of roots alters their morphology, cellular and biochemical responses, which results in reduced nutrient uptake and adaptability upon additive stress stimuli. In this review, we summarize recent methods that allow the study of shaded roots under controlled laboratory conditions and discuss the observed changes in the results depending on the root illumination status.
Keywords: fyziologická adaptace; kořeny rostlin; Seedlings; abiotic stress; flavonols; Plant Roots; semenáček; Light; light escape mechanism; světlo; Plants; root growth; reactive oxygen species; Plant Proteins; Gene Expression Regulation, Plant; auxin; cytokinin; regulace genové exprese u rostlin; rostliny; direct root illumination; D-rootsystem; rostlinné proteiny; Adaptation, Physiological; dark-grown roots